High‐performance ZnO varistor ceramics prepared by arc‐induced flash sintering with low energy consumption at room temperature. (4th November 2021) - Wu, Angxuan; Zhu, Zhixiang; Wang, Xilin; Yan, Nianping; Zhou, Hongyang; Huang, Rongxia; Ma, Guoming; Jia, Zhidong; Wang, Liming
Abstract: The development of ultra‐high voltage transmission lines requires a ZnO arrester with excellent electrical response and high voltage gradient. Compared with conventional preparation methods, flash sintering allows fast production of novel high‐performance ZnO varistor ceramics with low energy consumption and controlled grain growth. Herein, ZnO varistor ceramics were prepared using the flash sintering method at an air pressure of 21 kPa for 60 s at 25°C. The results showed that the flash‐sintered samples had fine grains and reduced loss of volatile elements. Moreover, the voltage gradient, leakage current density, and non‐linear coefficient of the flash‐sintered varistor ceramics were significantly improved compared with those of conventionally sintered samples. Owing to the short preparation time and absence of a heating process, the energy consumption of the proposed flash sintering method was significantly reduced to 10% of that by conventional sintering. The proposed method is a promising approach for the preparation of ZnO arresters with excellent electrical properties and serves as an effective method that realises energy saving and emission reduction.